A rare case of pituitary carcinoma with bone metastases: Ga-68-DOTATATE PET/CT findings - FİLİZOĞLU, NUH; ÖZGÜVEN, SALİH (My University, 2022)
Pituitary carcinomas are extremely rare and aggressive tumors that comprise only 0.2% of all pituitary tumors. Because of its rarity, pituitary carcinomas are difficult to diagnose. Conventional imaging methods are inadequate to detect metastatic lesions. Pituitary carcinomas are neuroendocrine tumors and express somatostatin receptors; therefore, Ga-68-DOTATATE PET/CT may be used in the staging of these rare tumors. Herein, we present an exceptional case of pituitary carcinoma with sclerotic skeletal metastases showing Ga-68-DOTATATE uptake.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nükleer Tıp; Medicine; Health Sciences; Internal Medicine Sciences; Nuclear medicine; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Klinik Tıp; Klinik Tıp (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; CLINICAL MEDICINE; Clinical Medicine (MED); Radiology, Nuclear Medicine and Imaging; Radiological and Ultrasound Technology; pituitary carcinoma; Ga-68-DOTATATE; PET/CT; metastasis